Stem-like CD8+ T cells in cancer - Steiner, Chelsea; Denlinger, Nathan; Huang, Xiaopei; Yang, Yiping (Frontiers in Immunology, 2024)
Stem-like CD8 + T cells (TSL) are a unique subset of immune cells that exhibit increased persistence and antitumor immunity. They are TCF1 + PD-1 + and are essential for the antitumoral response in response to checkpoint blockade immunotherapy. TSL cells have stem-like properties similar to memory T cell populations and can give rise to effector T cell populations to induce tumor control. This review will cover the current research on the formation, expansion, differentiation, and maintenance niches required for the TSL population in cancer. We will also discuss clinical implications in generating these cells or enhancing stemness in current therapeutic approaches.